Einstein y el arte de montar en bicicleta : buscando el equilibrio en el mundo moderno - Irvine, Ben, 1979- (Tiempo de mirar, 2016)
Einstein and the Art of Mindful Cycling shines new light onto one of the great scientific icons, and explores how pushing that pedal can nurture mindfulness in a spiritually stressful age. The author steers us through his own perspective on cycling - weaving the philosophical, practical and personal into an elegant balance. Add in a sprinkling of meditative insights, and we can all learn how to experience Einstein's enlightened outlook on life through the simple joy of riding a bicycle.